2020
DOI: 10.1007/s12571-020-01098-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-household decision-making, production diversity, and dietary quality: a panel data analysis of Ethiopian rural households

Abstract: Considering that rural poor are mostly subsistence farmers, it seems plausible that production diversity could lead to better nutrition for these farmers. The association between production and dietary diversity is complex, and this complexity demands rigorous empirical analyses and more attention to gendered aspects of intra-household decision-making. We employ panel data analyses of 363 Ethiopian smallholders surveyed in 2014 and 2016 to test for this phenomenon, and to explore the association of women's par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In the same manner, Table 3 shows that the middle wealth group households have 3 times more chance of consuming diverse foods compared to the poorest group (P <0.01). This finding is in line with the study of [34][35][36]. It is intuitive that rich households have better purchasing power to access a variety of foods and also engage in the production of diversified food items.…”
Section: Wealth Indexsupporting
confidence: 88%
“…In the same manner, Table 3 shows that the middle wealth group households have 3 times more chance of consuming diverse foods compared to the poorest group (P <0.01). This finding is in line with the study of [34][35][36]. It is intuitive that rich households have better purchasing power to access a variety of foods and also engage in the production of diversified food items.…”
Section: Wealth Indexsupporting
confidence: 88%
“…The much lower average wealth of Ethiopian households (nearly half the average of Vietnamese households), and reliance on subsistence production (consuming on average twice the proportion of household food from own harvest relative to Vietnam) may in part account for the statistically significant associations observed between crop diversity and child diet diversity in Ethiopia. A related study from Ethiopia also found that the association of crop diversity and dietary diversity was most important for the poorest households, as represented by limited non-farm income (64) . Ethiopia's lack of accessible agricultural markets, vulnerability to climate change and limited transportation infrastructure, contributing to widespread poverty among smallholder farmers and high levels of subsistence production, may mean that crop diversification has a greater potential nutritional benefit in this context (40,50) .…”
Section: Effect Modification By Household Wealth and Farm Market Orientationmentioning
confidence: 89%
“…Both quantitative and descriptive techniques were employed to analyse the data. The women's land-related bargaining power was captured following Sariyev et al (2017) women's participation in decision-making index (WPDMI). PCA was used to generate WPDMI combining 10 land-related decision-making variables capturing key decision domains within a household.…”
Section: Methodsmentioning
confidence: 99%